Maligni teratom mediastina--kazuistika - Veselý, M; Pestál, A; Dolezel, J; Jedlicka, V; Capov, I; Chovanec, Z; Veverková, L; Hermanová, M (Rozhledy v chirurgii, 2009)
In this case report the authors present a case of mediastinal malignant teratoma of a 23 years old patient, who suddenly suffers form chest pain as the only symptom. During examination is a huge mediastinal tumor diagnosed. After histological diagnosis is a radical surgery performed. According to the definitive histology is an adjutant oncological treatment indicated. The aim of our report is to think always about the mediastinal tumors as one of the possible cause of thoracic pain.
Keywords: Teratoma; Chest Pain; mužské pohlaví; Young Adult; dospělí; Humans; teratom; Adult; mladý dospělý; nádory mediastina; bolesti na hrudi; Mediastinal Neoplasms; lidé; Male